The Eudaimonic Functions of Music Listening Scale: An Instrument to Measure Transcendence, Flow and Peak Experience in Music - Groarke, Jenny M.; Hogan, Michael J. (Frontiers in Psychology, 2020)
There are many adaptive functions of music listening that are relevant for understanding wellbeing. Functions relating to mood and emotion regulation dominate general measures of music listening functions. Eudaimonic functions of music listening have been identified, but no scale has been developed to measure these functions. The current study reports on the development of a new measure to assess eudaimonic music listening functions. Items were developed based on a prior qualitative study and a literature review focused on music listening and wellbeing. The factor structure was investigated by EFA and CFA in a large sample of participants (N = 637, 17–66 years, M = 22.04, SD = 6.23, 326 males). Tests of dimensionality revealed a 3 factor scale with 7 items. The scale and its subscales possess good internal consistency. The Eudaimonic Functions of Music Listening scale measures Transcendence, Flow, and Peak Experience. Contrary to expectations eudaimonic FML did not relate to higher wellbeing (higher positive affect, lower negative affect, higher life satisfaction), rather results suggest that these FML are associated with greater emotional experience more generally. This brief scale will have applications in research focused on music listening benefits, music selection preferences, and experimental and developmental effects of music listening on psychological outcomes.